Penerapan Metode ABC Dalam Sistem Informasi Manajemen Persediaan Pada Toko Lily Jaya - Nina Meliana; Siti Jaenah (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2022)
Inventory management at Lily Jaya Store currently only records incoming and outgoing goods inventory, has not been able to provide information on the most needed and not much needed items, how many requests from each user and who made the most requests for goods at Lily Jaya Stores . This problem is due to the fact that the method of controlling goods has not been implemented. The purpose of this study is to provide a solution through the study of several theories and observations in the field in the context of designing an inventory management information system using the ABC (Always Better Control) method. The system development methodology used is the SDLC (System Development Life Cycle) method, namely the waterfall method. The programming language used is the PHP programming language (Hypertext Preprocessor) and the Bootstrap framework for display design on the web, the JQuery framework and the codeigniter framework for the MVC (Model, View, & Controller) development model as well as data management database management using the MySQL DBMS. The results of the research at the Lili Jaya Store are the creation of a management information system that can facilitate the recording of inventory, which was originally manual by using paper or books, now using web-based digital media and using databases. Inventory management becomes more efficient because of the implementation of the ABC method. This management information system can help the Lily Jaya Store in managing goods such as warehouse mutations, controlling the amount of inventory that can be controlled according to class category, thereby minimizing the accumulation of an item because it is not sold and there are many requests for certain goods, apart from that from This ABC classification can determine the layout of goods in the warehouse based on class categories.